Bickerstaff encephalitis in childhood: a review of 74 cases in the literature from 1951 to today - Giaccari, Luca Gregorio; Mastria, Donatella; Barbieri, Rosella; De Maglio, Rossella; Madaro, Francesca; Paiano, Gianfranco; Pace, Maria Caterina; Sansone, Pasquale; Pulito, Giuseppe; Mascia, Luciana (Frontiers in Neurology, 2024)
Bickerstaff brainstem encephalitis (BBE) is a rare autoimmune disease characterized by the subacute onset of bilateral external ophthalmoplegia, ataxia, and decreased level of consciousness. BBE is part of a group of rare autoimmune diseases in children that can affect the nervous system at any level. The onset of neurological deficits is often sudden and nonspecific. The diagnosis is based on clinical findings and abnormal findings on cerebrospinal fluid (CSF), electroencephalography (EEG), electromyography (EMG), and magnetic resonance imaging (MRI). BBE is associated with the presence of the antiganglioside antibody, anti-GQ1b and anti-GM1. Intravenous immunoglobulin (IVIg) and plasma exchange are often used as treatments for these patients.We conducted a review on clinical presentation, diagnosis, treatment and outcome of reported cases of BBE. 74 cases are reported in the literature from the first cases described in 1951 to today. The prevalence is unknown while the incidence is higher in males. In 50% of cases, BBE occurs following respiratory or gastrointestinal tract infections. The most frequent initial symptoms were c onsciousness disturbance, headache, vomiting, diplopia, gait disturbance, dysarthria and fever. During illness course, almost all the patients developed consciousness disturbance, external ophthalmoplegia, and ataxia.Lumbar puncture showed pleocytosis or cytoalbuminological dissociation. Abnormal EEG and MRI studies revealed abnormalities in most cases. Anti-GQ1b antibodies were detected in more than half of the patients; anti-GM1 antibodies were detected in almost 40% of patients. Treatment guidelines are missing. In our analysis, steroids and IVIg were administered alone or in combination; as last option, plasmapheresis was used. BBE has a good prognosis and recovery in childhood is faster than in adulthood; 70% of patients reported no sequelae in our analysis.Future studies need to investigate pathogenesis and possible triggers, and therapeutic possibilities.